1991
DOI: 10.1128/jb.173.17.5532-5538.1991
|View full text |Cite
|
Sign up to set email alerts
|

marA, a regulated locus which controls expression of chromosomal multiple antibiotic resistance in Escherichia coli

Abstract: Stable chromosomal multiple-antibiotic-resistant (Mar) mutants of Escherichia coli, derived by exposing susceptible cells to low concentrations of tetracycline or chloramphenicol, express cross-resistance to structurally unrelated antibiotics. The entire resistance phenotype is reversed to susceptibility by insertion of transposon Tn5 into a locus, designated marA, near 34 min on the chromosome (A. M. George and S. B. Levy, J. Bacteriol. 155:541-548, 1983). Strains in which 39 kbp of chromosomal DNA, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
175
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(182 citation statements)
references
References 30 publications
6
175
1
Order By: Relevance
“…It has been demonstrated that the accumulation of marA mRNA is increased by exposure of cells to either tetracycline, chloramphenicol, or salicylate (8,9,20). To determine if aarP mRNA accumulation was also increased by these agents, the accumulation of aarP mRNA was examined by Northern blot analysis after treating cells for 1.5 h with either chloramphenicol (2 g/ml), tetracycline (50 g/ml), or salicylate (5 mM).…”
Section: Identificationmentioning
confidence: 99%
“…It has been demonstrated that the accumulation of marA mRNA is increased by exposure of cells to either tetracycline, chloramphenicol, or salicylate (8,9,20). To determine if aarP mRNA accumulation was also increased by these agents, the accumulation of aarP mRNA was examined by Northern blot analysis after treating cells for 1.5 h with either chloramphenicol (2 g/ml), tetracycline (50 g/ml), or salicylate (5 mM).…”
Section: Identificationmentioning
confidence: 99%
“…The fact that the mar pathway is inducible by certain aromatic weak acids (7) and antibiotics (2,15) at relatively lower temperatures may mean that mar is primarily an adaptation to free-living situations. In contrast, the soxRS pathway has recently been shown to be stimulated by the biological signal molecule nitric oxide and to confer resistance to mouse macrophages (27).…”
mentioning
confidence: 99%
“…Previous work has shown that, independently of soxRS, the soxQl and cfxBl mutations cause transcriptional activation of some of the soxRS regulon genes and the induction of seven other proteins not influenced by soxRS or elevated by oxidative stress (14). Both soxQl and cfxBl, together with the previously identified marRi, map to the 34-min locus on the E. coli chromosome (6,13,14,19), which has been implicated in chromosome-mediated multiple antibiotic resistance (mar) (6,13,16). The soxQl-and the cfxBl-dependent phenotypes do not depend on the soxRS locus, and gene induction by soxRS in response to redox stress does not depend on mar (14).…”
mentioning
confidence: 99%